Study of the effect surface treatment of kenaf fiber on mechanical and water absorption of kenaf filled unsaturated polyester composite / \c Ilyas Ammer Saeid Salem. - Salem, Ilyas Ammer Saeid (School of Materials Engineering, Universiti Malaysia Perlis, 2017)
The research objectives are to investigate the effect of kenaf fiber loading on mechanical properties of kenaf/unsaturated polyester composites ; to determine the effect of treatment of kenaf fiber with stearic acid by applying different concentrations of stearic acidon mechanical properties of kenaf/unsaturated polyester composites ; to characterizestructure, morphology,determine the water absorption of treated and untreated kenaf /unsaturated polyester composites.